One-Step (18)F-Labeling and Preclinical Evaluation of Prostate-Specific Membrane Antigen Trifluoroborate Probes for Cancer Imaging - Kuo, Hsiou-Ting (J Nucl Med, 2019)
After the identification of the high-affinity glutamate-ureido scaffold, the design of several potent (18)F- and (68)Ga-labeled tracers has allowed spectacular progress in imaging recurrent prostate cancer by targeting the prostate-specific membrane antigen (PSMA). We evaluated a series of PSMA-targeting probes that are (18)F-labeled in a single step for PET imaging of prostate cancer. Methods: We prepared 8 trifluoroborate constructs for prostate cancer imaging, to study the influence of the linker and the trifluoroborate prosthetic on pharmacokinetics and image quality. After 1-step labeling by (19)F–(18)F isotopic exchange, the radiotracers were injected in mice bearing LNCaP xenografts, with or without blocking controls, to assess specific uptake. PET/CT images and biodistribution data were acquired at 1 h after injection and compared with (18)F-DCFPyL on the same mouse strain and tumor model. Results: All tracers exhibited nanomolar affinities, were labeled in good radiochemical yields at high molar activities, and exhibited high tumor uptake in LNCaP xenografts with clearance from nontarget organs. Most derivatives with a naphthylalanine linker showed significant gastrointestinal excretion. A radiotracer incorporating this linker with a dual trifluoroborate-glutamate labeling moiety showed high tumor uptake, low background activity, and no liver or gastrointestinal track accumulation. Conclusion: PSMA-targeting probes with trifluoroborate prosthetic groups represent promising candidates for prostate cancer imaging because of facile labeling while affording high tumor uptake values and contrast ratios that are similar to those obtained with (18)F-DCFPyL.